Bim-based research framework for sustainable building projects: A strategy for mitigating bim implementation barriers - Manzoor, B. (MDPI AG, 2021)
Although Building Information Modeling (BIM) can enhance efficiency of sustainable building projects, its adoption is still plagued with barriers. In order to incorporate BIM more efficiently, it is important to consider and mitigate these barriers. The aim of this study is to explore and develop strategies to alleviate barriers in developing countries, such as Malaysia, to broaden implementation of BIM with the aid of quantitative and qualitative approaches. To achieve this aim, a comprehensive literature review was carried out to identify the barriers, and a questionnaire survey was conducted with construction projectsâ stakeholders. The ranking analysis results revealed the top five critical barriers to be âunavailability of standards and guidelinesâ, âlack of BIM trainingâ, âlack of expertiseâ, âhigh costâ, and âlack of research and BIM implementationâ. Comparative study findings showed that âlack of research and BIM implementationâ is the least important barrier in other countries like China, United Kingdom, Nigeria, and Pakistan. Furthermore, qualitative analysis revealed the strategies to mitigate the BIM implementation barriers to enhance sustainable goals. The final outcome of this study is the establishment of a framework incorporated with BIM implementation barriers and strategies namely, the âBIM-based research frameworkâ, which can assist project managers and policymakers towards effective sustainable construction. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.